The concept of elasticity and strategies for teaching it in introductory courses of economics (2019)
This article presents a geometric and algebraical approach to teach the concept of elasticity for undergraduate students with different levels of knowledge in mathematics and pointing out why it is necessary to introduce it from the idea of he slope of a function. To achieve this objective a short review of the literature of the main properties associated with elasticity is carried out, without separating them from their historical development, to illustrate a way of presenting the concept in a discrete or continuous way and using geometric arguments or algebraic expressions. Due to the flexibility of the concept, and taking into account the previous knowledge of the student, it is concluded that this approach is a more adequate way to teach the concept.